Modeling river sediment deposition into The Kenyir Reservoir, Malaysia - Abood, Manal M. (2012)
Assessment of the amount of sediment inflow from the Berang river and the Kenyie river and the total quantity deposited to the Kenyir reservoir was made. Kenyir reservoir is the biggest man-made lake in Southeast Asia. Kenyir dam and reservoir are mainly designed for hydroelectric power generation and flood mitigation purposes. This study was made to find an alternative solution to monitor the elevation changes with less cost and less efforts by using a computer program that can simulate the elevation accurately. For this purpose, the GSTARS3 program has been chosen. Due to limitation on data available, the prediction was undertaken using the hydrological modeling (HECHMS program) to fill the missing data in historical record and obtain a full set of data that is used in sediment transport modeling (GSTARS3 program). GSTARS3 wa integrated with GIS to display the output as sequences of grids. ArcView was used to convert the GSTARS3 output to Arc View GIS grid format. GSTARS3 program was validated using two terms of validation, short term validation (ST validation ) for the period from 1995 to 1998, and long term validation (LT validation) for the period from 1995 to 2006 for both Berang river and Kenyir river thalweg profiles and their selected cross sections. The results show a good agreement between the simulated and measured data with an error ranges from 5.5 % to 13.1 % for short term validation and ranges from 6.3 % to 14.7 for long term validation for both Berang and Kenyir rivers. Although, LT validation errors have higher values than that in ST validation, they have not increased more than 15 % in all cases. Statistical analysis was applied to check the accuracy of HEC-HMS output. The results show a reasonable agreement with an errors equal to 0.41 m3/sec for Berang basin and equal to 0.67 m3/sec for Kenyir basin. It was found that the combination of two programs (HEC-HMS and GSTARS3) helps to simulate the sediment when the hydrological data is limited and the results show that the computed values agreed well with the historical recorded data for the thalweg profiles and selected cross sections.